Modern treatment of endometrial local hyperplastic processes from positions of the pathogenic approach - V. O. Benyuk; Y. V. Kravchenko; T. V. Kovaliuk; S. V. Beniuk; I. A. Usevych (Publishing House TRILIST, 2020)
Purpose of research: to improve the treatment effectiveness of patients with endometrial local hyperplasia by use of endoscopic technologies and pathogenetical postoperative therapy. Materials and methods. 66 women whose treatment algorithm included 4 stages (hysteroscopic polyp ablation followed by the morphological study, hormonal therapy aimed at the endometrium suppression, hormonal status optimization and dispensary observation within 5 years) were the subject of the study. After complex examination and histological verification of endometrial polyposis diagnosis patients were divided into two groups: A (n = 34) with the immune corrective therapy and B (n = 32). Examination algorithm included the endometrial immune histochemical examination with its immune histochemical profile definition. Study results. Histological screening of endometrium state resulted that 9 (26.5%) patients in the A group had the chronic endometritis features. The corresponding index for the B group stood for 15 patients (46.9%) that is 20.4% higher compared to the A group. Estrogen receptors expression with the background of progestogen treatment indicated the 1.2 times lowering for both groups. The viral and bacterial complex screening indicated the endometrial pathogenic contamination dramatic decrease. Study of tumor necrosis factor's level determined the straightforward tendency with the CD 138 index dynamics. In a year term the complete treatment effect in A group was observed among 29 patients (85.2%), and the endometrial polyposis recurrence was observed among 5 (14.8%) patients. Conclusions. It is necessary to take into account the woman's age, joint genital and somatic pathology's presence and the immune histochemical profile of hyperplastic endometrial while determining the endometrial pathology differentiated treatment tactics. Additional immune corrective therapy with the antibacterial treatment determines the receptor phenotype restoration, normalization of tumor necrosis factor-α lever and increases the endometrial polyposis treatment effectiveness up to 22.7%.